Resistance of the cattle tick Rhipicephalus (Boophilus) microplus to ivermectin in Argentina - Torrents, Jorgelina; Sarli, Macarena; Rossner, Maria Victoria; Toffaletti, Jose Rodolfo; Morel, Nicolas; Martinez, Norberto Claudio; Webster, Anelise; Mangold, Atilio Jose; Guglielmone, Alberto; Nava, Santiago (Elsevier, 2020)
Resistance to ivermectin in populations of the cattle tick Rhipicephalus microplus in Argentina was diagnosed in this work. The in vitro larval immersion test (LIT) was used to determine quantitatively the levels of resistance to ivermectin in different populations of R. microplus. Additionally, field trials to control natural infestations of R. microplus on cattle with a commercial formulation of ivermectin 3.15% were carried and jointly analyzed with the in vitro assays. The phenotypic response of the populations analyzed was not uniform. Five of them were classified as susceptible, four populations as resistant, and one in the category “incipient resistance”. Regarding the field trials, the therapeutic efficacy in a population classified with LIT as susceptible achieved values higher than 94% two weeks after treatment, and no reproductively viable females were observed after the second day post-treatment. Conversely, the values of efficacy percentage in a population (named as “San Martín”) classified with LIT in the category “incipient resistance” never exceeded the 70.8%, and engorged females were collected in practically all counts. The population “San Martín” was classified in the category “incipient resistant” with LIT analysis, but the field trial unambiguously shows that this tick population is resistant. The comparison of the results obtained with LIT in vitro assays and through field trials shows that biased estimations of resistance levels may occur when resistance ratios (RR) values are ≤2, and additional field efficacy trials could be needed to know with precision the status of the tick populations evaluated.